KLASIFIKASI PENGEMUDI YANG TERDISTRAKSI DENGAN ALGORITMA SUPPORT VECTOR MACHINE BERDASARKAN PENGURANGAN FITUR PCA dan CNN - Alfajr, Achmad Yuneda; Kartini, Kartini; Sari, Anggraini Puspita (Universitas Nusa Cendana, 2023)
The use of ground transportation in Indonesia, especially in major cities like Surabaya, has experienced rapid growth. However, this increased usage has also led to a rise in traffic accidents. One of the main contributing factors is driver distraction. Therefore, this study aims to develop a method for detecting distracted drivers using image classification technology with Convolutional Neural Networks (CNN) and Support Vector Machine (SVM) models. In this research, data was obtained from the